Magnesium Sulfate Poisoning Revealed by Hypothermia and Visual Disturbances: About a Case - D, Barboza; V, William; M M, Traoré; PA, Leye; M, Diaw; P I, Ndiaye; EB, Ba; I, Gaye; MD, Bah; M L, Fall; E, Diouf (International Journal of Innovative Research in Medical Science, 2018)
Eclampsia requires appropriate treatment of pregnancy-induced hypertension and early management before the onset of signs of seriousness. Patients in post-caesarean section are transferred to intensive care. Magnesium sulfate is the drug of choice because it reduces the incidence of eclampsia attacks in severe pre-eclamptic patients and the risk of recurrent seizures in eclamptic patients. Like any medicine, it has side effects, some of which may go unnoticed. This is a 30-year-old primip female patient at the maternity hospital for severe pre-eclampsia. Blood pressure was 180/130 mmHg. The patient had severe vertigo and edema. She was put under magnesium sulfate (MgSO4) at a rate of 4g in 20 minutes then 1g / h in pre and post-caesarean section. At the twelfth hour after admission to intensive care, she presented visual blur and persistent hypothermia. The course of action consisted in stopping magnesium sulfate and administering 2g of calcium gluconate. The evolution was favorable with a return to normal temperature and a good quality vision. The electrocardiogram was normal. She was transferred to the maternity ward at day 6.